Rubus coreanus Enhances Peri-Implant Bone Healing and Biomineralization in Ovariectomized and Healthy Rats - Monteiro, Naara Gabriela [UNESP]; de Oliveira-Filho, Odir Nunes [UNESP]; Gandolfo, Maria Isabela Lopes [UNESP]; da Silva, Ana Cláudia Ervolino [UNESP]; Pitol-Palin, Letícia [UNESP]; Botacin, Paulo Roberto [UNESP]; Santos, Gabriel Mulinari dos [UNESP]; de Souza Batista, Fábio Roberto [UNESP]; Okamoto, Roberta [UNESP] (MDPI, 2025)
Estrogen deficiency contributes to osteoporosis and can therefore compromise the peri-implant bone. Hence, this study evaluated peri-implant bone healing when Rubus coreanus (RC) was administered orally in ovariectomized and healthy rats. Forty 4-month-old female rats were divided into four groups: SHAM (healthy rats), SHAM/RC (healthy rats treated with RC), OVX (ovariectomized rats), and OVX/RC (ovariectomized rats treated with RC). The oral administration of RC started thirty days after ovariectomy, and implant placement into the rat tibia occurred ninety days after the ovariectomy. Euthanasia occurred sixty days after implantation. The analyses performed included removal torque, RT-PCR, confocal microscopy, and immunolabeling. A significance level of p < 0.05 was considered for all tests. The highest reverse torque values were observed in the SHAM/RC group, followed by the OVX/RC group. Confocal microscopy showed the greatest bone biomineralization in the SHAM/RC group, followed by the OVX/RC group. RT-PCR data indicated that RC decreased the RANKL/OPG ratio in both conditions. Immunohistochemistry demonstrated a balance between bone formation and resorption in all groups, especially stimulating osteoblastogenesis in both treated groups. In conclusion, RC enhanced peri-implant bone healing and biomineralization in both healthy and ovariectomized rats, with stronger effects in healthy rats, suggesting that estrogen may enhance its efficacy. These findings support RC's potential as a prophylactic and therapeutic agent.